Steroid receptor RNA activator protein binds to and counteracts SRA RNA-mediated activation of MyoD and muscle differentiation - Hubé, Florent (Oxford University Press, 2011)
The steroid receptor RNA activator (SRA) has the unusual property to function as both a non-coding RNA (ncRNA) and a protein SRAP. SRA ncRNA is known to increase the activity of a range of nuclear receptors as well as the master regulator of muscle differentiation MyoD. The contribution of SRA to either a ncRNA or a protein is influenced by alternative splicing of the first intron, the retention of which disrupts the SRAP open reading frame. We reported here that the ratio between non-coding and coding SRA isoforms increased during myogenic differentiation of human satellite cells but not myotonic dystrophy patient satellite cells, in which differentiation capacity is affected. Using constructs that exclusively produce SRA ncRNA or SRAP, we demonstrated that whereas SRA ncRNA was indeed an enhancer of myogenic differentiation and myogenic conversion of non-muscle cells through the co-activation of MyoD activity, SRAP prevented this SRA RNA-dependant co-activation. Interestingly, the SRAP inhibitory effect is mediated through the interaction of SRAP with its RNA counterpart via its RRM-like domain interacting with the functional sub-structure of SRA RNA, STR7. This study thus provides a new model for SRA-mediated regulation of MyoD transcriptional activity in the promotion of normal muscle differentiation, which takes into account the nature of SRA molecules present.